Using consecutive Rapid Participatory Appraisal studies to assess, facilitate and evaluate health and social change in community settings - Murray Scott A; Lloyd Simon; Brown Colin S (BMC, 2006)
Abstract Background To investigate how a relatively socio-economically deprived community's needs have changed over time, assess which recommendations from an earlier assessment were implemented and sustained, and consider whether serial Rapid Participatory Appraisal is an effective health research tool that can promote community development and has utility in assessing longitudinal change. Methods Rapid Participatory Appraisal involves communities in identifying and challenging their own health-related needs. Information on ten health and social aspects was collated from existing documentation, neighbourhood observations, and interviews with a range of residents and key informants, providing a composite picture of the community's structure, needs and services. Results The perceived needs after 10 years encompassed a wide construct of health, principally the living environment, housing, and lack of finance. Most identified upstream determinants of health rather than specific medical conditions as primary concerns. After the initial Rapid Participatory Appraisal many interviewees took the recommendations forward, working to promote a healthier environment and advocate for local resources. Interventions requiring support from outwith the community were largely not sustained. Conclusion Rapid Participatory Appraisal proved valuable in assessing long-term change. The community's continuing needs were identified, but they could not facilitate and sustain change without the strategic support of key regional and national agencies. Many repeatedly voiced concerns lay outwith local control: local needs assessment must be supported at higher levels to be effective.